2017
DOI: 10.18632/oncotarget.15739
|View full text |Cite
|
Sign up to set email alerts
|

Association between BRCA1 P871L polymorphism and cancer risk: evidence from a meta-analysis

Abstract: Breast cancer 1 (BRCA1) gene makes great contributions to the repair of DNA. The association between BRCA1 P871L polymorphism and cancer risk has been investigated in a growing number of studies, but the conclusions are not conclusive. To obtain a comprehensive conclusion, we performed a meta-analysis of 24 studies with 13762 cases and 22388 controls. The pooled results indicated that BRCA1 gene P871L variant decreased risk of overall cancer (homozygous model: odds ratio (OR) = 0.89, 95%confidence interval (CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…A meta-analysis of 24 studies consisting of 13762 cases and 22388 controls has found no association between BRCA1 p.P871L and risk of breast cancer. Despite the fact that this polymorphism leads to substitution of amino acid proline to leucine at position 871, which is part of interaction region for another critical homologous recombination protein called RAD51 and has been considered to confer cancer susceptibility, they observed a significant association with decreased risk of overall cancer in either homozygous or heterozygous condition [27]. There were no polymorphisms observed in TP53, PTEN, CDH1, CHEK2 and XRCC2.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A meta-analysis of 24 studies consisting of 13762 cases and 22388 controls has found no association between BRCA1 p.P871L and risk of breast cancer. Despite the fact that this polymorphism leads to substitution of amino acid proline to leucine at position 871, which is part of interaction region for another critical homologous recombination protein called RAD51 and has been considered to confer cancer susceptibility, they observed a significant association with decreased risk of overall cancer in either homozygous or heterozygous condition [27]. There were no polymorphisms observed in TP53, PTEN, CDH1, CHEK2 and XRCC2.…”
Section: Discussionmentioning
confidence: 93%
“…The possible hypothesis behind cancer occurrence despite the presence of p.K1183R polymorphism in our studied cases could be the balance between DNA damage and repair that determines the individual susceptibility to breast cancer. DNA damages caused by certain environmental factors such as those of chemicals and radiations that are not repaired fully could wake the genomes stability leading to carcinogenesis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in a Czech population (Soucek et al, 2007), where no association was reported. Meta-analyses carried out in 2014 (Qin et al, 2014) and 2017 (Miao et al, 2017) reported no association of the p.Pro871Leu polymorphism and breast cancer risk. Contradictory results have also been reported for the BRCA1 871L allele, as significantly associated with increased risk of breast cancer in a Polish population (Smolarz et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…The four variants of BRCA1 [c.190T>C (p.Cys64Arg), 1307delT, g.5331G>A (p.G1738R) and c.2612C>T (p.Pro871Leu)] were investigated in the current study. The variant c.2612C>T (p.Pro871Leu) is a nonsynonymous polymorphism of BRCA1 that leads to the substitution of proline by leucine at position 871, a region where recombinase RAD51 interacts with BRCA1 to aid homologous recombination (Miao et al, 2017). The T allele has been reported to show an association with breast cancer risk in Chinese populations (Xu et al, 2018) though some studies have reported no significant association between the p.Pro871Leu variant of BRCA1 and breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…So, any deficiencies in BRCA1 may lead to genetic instability and tumor genesis. 18,30,31 BRCA1 gene is located on chromosome at 17q21 covering more than 80kb distributed in 22 exons and encoded for a protein of 1,863 amino acids that was mapped and cloned in 1994. 14,31 Among the Asian countries, Pakistan has the highest rate of breast cancer as well as ovarian cancer.…”
Section: Introduction Introductionmentioning
confidence: 99%